ONCE AGAIN ABOUT THE TIME AND CIRCUMSTANCES OF THE CREATION OF THE CHURCH OF ST. PANTELEIMON IN HALYCH - HOLOVKO, Oleksandr (Halych. Scientific work collection, 2023)
The article delves into the initial period of the oldest preserved Christian building in the Prykarpattia region, the church of St. Panteleimon in the village of Shevchenkove near Halych. Over its more than eight centuries of existence, this religious structure not only changed its name but also embraced various Christian denominations. Notably, from the mid-14th to the mid-20th century, the monument served as the church of the revered St. Stanislav in Poland. The past of the ancient temple has piqued the interest of scientists, with its historiography spanning almost two hundred years. A particular focus within this research is the topic related to studying the initial stage of the temple’s existence, corresponding to the time of the Halych and Halych–Volyn Principalities. The scarcity of information in written records about the temple’s early history underscores the exceptional role of archaeological research in uncovering its fate. Researchers have dedicated considerable attention to the study of the church’s unique graffiti corpus. This article examines the circumstances and reasons for the cult of St. Panteleimon’s popularity in Rus, particularly among members of the princely family. The author revises the perspectives presented in previous publications, including his own assumptions, concerning the potential patron behind the construction of the temple. Analysis of available sources suggests that the idea and consecration of the church are attributed to Prince Yaroslav Volodymyrovych Osmomysl, with the direct construction executed by Yaroslav’s son, Volodymyr, in the early 90s of the 12th century. Subsequently, a princely residence developed around the temple, owned by princes Roman Mstyslavych and Mstyslav Mstyslavych «Udatnyi».